Surveying the Diffability in Game of Thrones - Parvaneh Shojaei; Hassan Shahabi (Indonesian Journal of Disability Studies, 2018)
In every society people with differences in their physiques and abilities are known as people with disabilities-People First Model, even in the Conventions about the Right of the People with Disabilities. This paper tries to study people with different physiques and abilities in Game of Thrones which is created by David Benioff and D. B. Weiss, an adaptation of George R. R. Martin's fantasy novels, A Song of Ice and Fire. This article studies the Social Model of disability which has been organized as a one-dimensional standard society. This model focuses on disability as a social not individual problem. Based on social model of disability, this paper discusses diff-ability and introduces new binary opposition of diff-ability/sim-ability for disability/non-disability. Struggle between standard society for people with similar physiques and abilities and dis-standard society for people with different physiques and abilities which is obvious in this novel, clearly illustrates how the environment of the society affects the fate and the condition of these people. Considering universal popularity of Game of Thrones and the fact that choice of characters with different physiques and abilities can hardly be incidental and that literary works as cultural artifacts and binary oppositions, which are culturally constructed, this paper attempts to transform negative attitudes of society and create positive attitudes toward this population. Positive terminologies, by emphasizing on abilities, create positive attitudes toward people with different physiques and abilities, and negative terminologies produce negative ones. The disability is a kind of "problem" which has source in society. By making society standard for the diff-abled, they would be able as well as the sim-abled people.